2018
DOI: 10.1371/journal.pone.0208116
|View full text |Cite
|
Sign up to set email alerts
|

Health problems during childhood and school achievement: Exploring associations between hospitalization exposures, gender, timing, and compulsory school grades

Abstract: AimsTo investigate while accounting for health at birth 1) associations between health problems during childhood, measured as hospitalizations, and school achievement in the final year of compulsory school, measured as overall grade points and eligibility for upper secondary education, 2) if and how gender moderates the association between health problems and school achievement, 3) if and how the timing of a health problem during childhood is associated with later school achievement.MethodsAnalyzes were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Respiratory failure due to asthma or bronchiolitis was associated with a lower burden of school absence than respiratory failure due to pneumonia, sepsis, or other causes. Previous studies have shown that hospitalization for acute medical conditions, including infections, burns, transplant, and diabetes, are associated with subsequent absenteeism and lower academic achievement. Similarly, chronic health conditions and special health care needs (eg, prescription medications, specialized medical care, or educational services) are associated with school absence …”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure due to asthma or bronchiolitis was associated with a lower burden of school absence than respiratory failure due to pneumonia, sepsis, or other causes. Previous studies have shown that hospitalization for acute medical conditions, including infections, burns, transplant, and diabetes, are associated with subsequent absenteeism and lower academic achievement. Similarly, chronic health conditions and special health care needs (eg, prescription medications, specialized medical care, or educational services) are associated with school absence …”
Section: Discussionmentioning
confidence: 99%
“…Complementary support such as social services and educational services should also be available for children. Otherwise, hospitalization can have a long-term negative impact on children's performance at school and potentially lead to inequalities in education (Bortes et al, 2018). In the United Kingdom, an innovative solution for children with long-term diseases missing school has come in the form of a robot to connect the child with the classroom and classmates (No Isolation Project).…”
Section: Discussionmentioning
confidence: 99%
“…Mental and physical health symptoms can compound one another, leading to a vicious cycle of chronic comorbidities [ 7 ]. Consequently, children and young people living with chronic conditions and their sequelae often experience limitations in their participation in school [ 8 ] and social activities [ 9 , 10 ] and difficulties in family relationships [ 11 ], in addition to the strain of treatment and physical symptoms such as pain and fatigue [ 12 ].…”
Section: Introductionmentioning
confidence: 99%